A framework for the risk assessment of residual hazardous material in the dynamic environment of a composite production process considering operational time variation. Issue 1 (17th July 2020) - Asgari, Alireza; Kibala, Muke; Beauregard, Yvan
Abstract: In the chemical product production process, activities relating to the transportation and storage of residual hazardous materials increase the risk of workplace contamination and associated negative impacts on worker health and safety. In this context, the dynamic nature of the process complicates the study of the parameters underlying the related operational risks. The current operational risks assessment standard, ISO 31000, cannot provide a practical pathway to assess risks in dynamic operational environments. We, therefore, model a dynamic environment to investigate the effect of functional time variation on risk assessment. Verification of the claimed effect will show that even with rigorous instruction when using the available equipment, the process cannot fully conform to current safety standards.